2021
DOI: 10.1073/pnas.2026104118
|View full text |Cite
|
Sign up to set email alerts
|

AGO2 promotes tumor progression in KRAS-driven mouse models of non–small cell lung cancer

Abstract: Lung cancer is the deadliest malignancy in the United States. Non–small cell lung cancer (NSCLC) accounts for 85% of cases and is frequently driven by activating mutations in the gene encoding the KRAS GTPase (e.g., KRASG12D). Our previous work demonstrated that Argonaute 2 (AGO2)—a component of the RNA-induced silencing complex (RISC)—physically interacts with RAS and promotes its downstream signaling. We therefore hypothesized that AGO2 could promote KRASG12D-dependent NSCLC in vivo. To test the hypothesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Recently, small molecule inhibitors of KRAS G12C point mutations have shown promise in human trials ( 69 , 70 ); however, no specific inhibitors of mutant NRAS or HRAS have been successfully developed to date ( 71 ). With the goal of identifying potentially druggable interactors with mutant RAS proteins, our group recently identified the novel KRAS–AGO2 interaction ( 9 ) and described its role in promoting both pancreatic ( 11 ) and NSCLC ( 12 ). Importantly, this interaction was specific to AGO2 and not the other Argonaute isoforms ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, small molecule inhibitors of KRAS G12C point mutations have shown promise in human trials ( 69 , 70 ); however, no specific inhibitors of mutant NRAS or HRAS have been successfully developed to date ( 71 ). With the goal of identifying potentially druggable interactors with mutant RAS proteins, our group recently identified the novel KRAS–AGO2 interaction ( 9 ) and described its role in promoting both pancreatic ( 11 ) and NSCLC ( 12 ). Importantly, this interaction was specific to AGO2 and not the other Argonaute isoforms ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently extended these initial observations in a mutant Kras -driven mouse model of pancreatic ductal adenocarcinoma (PDAC) with co-knockout of Ago2 ( 11 ). Furthermore, Ago2 ablation in a mutant Kras- driven nonsmall cell lung cancer (NSCLC) mouse model significantly reduced tumor burden and altered downstream Kras signaling ( 12 ). These combined studies demonstrated an important role for the AGO2–RAS interaction in promoting a KRAS -driven oncogenic state.…”
Section: Introductionmentioning
confidence: 99%
“…The functions of AGO2 in tumorigenesis are diverse and range from high levels associated with poor prognosis in HCC [ 149 ], ovarian carcinoma [ 150 ], and gastric cancer [ 151 ], or mediating the elevation of oncogenic miR-378a-3p in Burkitt lymphoma [ 152 ], to its low expression as an indicator of poor prognosis in CRC patients [ 153 ]. AGO2 protein–protein interactions (e.g., KRAS and AGO2) are involved in the progression of pancreatic ductal adenocarcinoma [ 154 ] and NSCLC [ 155 ]. Studies of these multilevel effects are in progress and may offer patient specific targeted treatment, e.g., AGO2, as a delivery vehicle for inhibitory miRNAs [ 156 ].…”
Section: Cancer-associated Dna/rna Binding Proteinsmentioning
confidence: 99%
“…Activated Kras G12D refers to the successful Cre-mediated excision of the Lox-Stop sequence, allowing for transcription of the mutant Kras allele. To determine the tissue specific activation of the Kras G12D mutation, we followed the standard method first published by Hingorani [8,9] and further utilized by other groups working with this Lox-Stop-Lox conditional Kras mouse strain [10][11][12]. Genomic DNA was isolated from tail, pancreas, anus and anal tumor from KC mice.…”
Section: Genotyping For the Activation Of Kras G12d Mutation Constructmentioning
confidence: 99%